PELAKSANAAN PRODUKSI PRODUK HALAL FOOD MENGGUNAKAN AKAD KERJASAMA DI TINJAU DARI PRINSIP TABADUL AL-MANAFI DAN AN’TARADHIN - Neni Hardiati; Atang Abdul Hakim (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
Cooperation agreement in the principles of Tabadul al-manafi and An'taradhin is very effectively applied. For this is evident from the fundamentals of the law. This principle is aqidah, shari'ah and morals. This economic system is based on Islamic values, namely equality, usefulness, balance, kindness and universality (rahmat li al-aalmin), so that the people of Indonesia in the future experience improved economic welfare on the basis of sharia principles. According to thrifty authors that the cooperation agreement has the benefit to be applied to the actors of the production of halal food products. The source of the law that underlies all economic activities, and other philosophical foundations of Islamic law that form the basis in developing the Islamic economy anywhere and in any form, and should not be out of the sharia corridor. Benefit is the main objective in Islamic economic activities and avoids all forms of normality. Through this paper by qualitative research method, with normative juridical approach through literature study. So that with this method can be excavated filosifis values in the development of Islamic economy in the field of halal product production.